Peran Kepemimpinan Kepala Ruang Rawat terhadap Penerapan Budaya Keselamatan Pasien di Rumah Sakit - Hexanini, Clara Pelita Sri; Wahidi, Kemala Rita; Anindita, Rina (Lembaga Penerbitan Universitas Esa Unggul, 2021)
Introduction: In an effort to improve the quality and safety of patients, leaders / managers at the Hospital must be aware of and strive to build a patient safety culture. The application of effective communication is one of the important elements in building patient safety. The number of unexpected events is due to the implementation of effective communication that is not in accordance with the standard, resulting in the desired clinical message not reaching the expectations. The Head of Ward Nurse is a nursing manager who is directly related to health service activities at the Hospital. The Head of Ward Nurse as the lower manager is expected to be able to carry out all management functions so that the environment and working conditions will support nursing services in maintaining patient safety. This study uses quantitative research design with survey methods using questionnaires as instruments. Data analysis method uses Structural Equation Model (SEM). Respondents of this study were 180 nurses at the EMC Hospital in Tangerang. The results showed that the leadership role variable of the head of room had a positive effect on the application of the patient safety culture and the application of effective communication had a positive effect on the patient safety culture, and the leadership role of the room head had a positive effect on the implementation of patient safety culture.Keywords: Patient Safety Culture, Effective Communication, Leadership Role of Ward Nurse